2019
DOI: 10.17511/ijpr.2019.i01.05
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical and hematological profile in children with dengue fever in a teaching hospital in Telangana

Abstract: Introduction:The aim of the study was to determine the clinical and hematological profile in patients with Dengue fever. Materials and Methods: This was a prospective study done at Malla Reddy Medical College for Women, Telangana, for a period of six months. A total of 110 cases of dengue infection were studied. The patient demographics, clinical symptoms, hematological characteristics such as hemoglobin, total leucocyte count, platelet count, serological studies and abdominal ultrasound findings were noted. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…Anand et al [19] reported hepatomegaly in 57% of cases which is similar to our study but splenomegaly was seen only in children with concurrent malaria or Gram-negative infection. As per studies done by Sastry et al [20] and Sahana et al [21], more frequent association of organomegaly and fluid collection were reported in severe dengue than our study. Mishra et al [7] reported more GI bleed (76.9) in severe dengue group than ours.…”
Section: Discussionsupporting
confidence: 87%
“…Anand et al [19] reported hepatomegaly in 57% of cases which is similar to our study but splenomegaly was seen only in children with concurrent malaria or Gram-negative infection. As per studies done by Sastry et al [20] and Sahana et al [21], more frequent association of organomegaly and fluid collection were reported in severe dengue than our study. Mishra et al [7] reported more GI bleed (76.9) in severe dengue group than ours.…”
Section: Discussionsupporting
confidence: 87%
“…Non-severe dengue includes both DF and DFW and SD includes DHF/DSS. We had included age group from 1 to 12 years and maximum numbers of cases were seen in the age group >6 years of age (51%) and the least affected age group was 1-3 years of age (21%) which was similar findings to the many other studies like 5 The mean age group in this study was 6.8. More involvement in children > 6years could be explained by the diurnal adaptation of Aedes mosquito in stored water.…”
Section: Discussionsupporting
confidence: 82%